A solution to the problem of clinical supervision for lone allied health professionals within a hospice setting. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Andrew, Inga; Worsfold, Caroline; Storey, Frances; Tibbett, Sue
Abstract : Background: Clinical supervision has long been an integral part of practise within the nursing profession, and more recently with allied health professions, the benefits of which have been demonstrated in the literature. Within the Hospice setting, allied health professionals (AHPs) often work alone within their professional group. During informal discussions, AHPs at St. Benedict's Hospice found they were experiencing similar challenges and changes to their clinical practise. Aims: To establish a peer-led, AHPs, clinical supervision group. Method: All AHPs working for the Hospice, were invited to attend; chaplain, occupational therapist, physiotherapist (community), physiotherapist (Hospice), lecturer/practitioner, pharmacist, social worker. The social worker declined to participate due to different management structures. Monthly, hour long meetings were planned, with each member agreeing to facilitate sessions on a rota for a year. A basic structure was established, including that brief notes would be taken on the following; What were the issues/problems? Analyse the event Proposed actions following the event What is the main learning taken away from the event? Outcomes: Over the first year the mean number of participants per meeting was 4 (66%). The percentage of meetings participants attended ranged from 100 to 38%. The brief notes demonstrated participants sent apologies if unable to attend. After a year, participants all gave positive feedback, particularly about the benefits of supporting one another through times of great change within the NHS. The group was keen to continue and formally agreed an 'AHPs clinical supervision contract' including details of; ground rules, structure, documentation and evaluation. The success of the group continues, the mean percentage of AHPs at meetings this year is 75%. Conclusion: This well attended model of multidisciplinary clinical supervision could prove to be a solution to the problem of supervision for lone allied health professionals within a Hospice setting.